Dielectric and resonant Gain singularities in multilayered nanostructures - Caligiuri, Vincenzo; Carbone, Vincenzo; De Luca, Antonio (My University, 2017)
In this thesis work, the dielectric and gain singularity regimes in Hyperbolic Metamaterials (HMM) have been conceived and both theoretically and experimentally studied. For the first one it has been demonstrated how, in order to induce a dielectric singularity in the dielectric permittivities of an HMM specific conditions on both the geometry and optical properties of the fundamental metal/dielectric components have to be fulfilled. An HMM respecting these constrains is named Epsilon- Near-Zero-and-Pole (eNZP). Such a system manifests both the so-called Type I and Type II within the visible range and, noticeably, allows to cancel the usually found effective dielectric (or metallic) frequency gap betwen them, showing a inversion point of these two coexisting anisotropies, called Canalization Wavelength or Transition Wavelength. It has been demonstrated how a light wave propagating inside the eNZP HMM, remains perfectly subwavelength collimated, proceeding as a straight soliton for more than 100 Rayleigh lengths. Many fascinating new properties are unlocked in such regime, among which the supercollimation and the perfect lensing have been theoretically studied as well as experimentally demonstrated. Due to the specific stringent conditions to be respected, it has been demonstrated that with a classic two-component HMM it is not possible to tune the eNZP wavelength and a new configuration has to be adopted based on three components: a high index dielectric, a low index dielectric and a metal. By means of this new configuration, a full visible range design range of the eNZP wavelength has been demonstrated, keeping the same three fundamental materials and only acting on their thickness. The possibility of introducing thermal tunability of the optical features of a classic HMM has been demonstrated, thus overcoming the well known lack of tunability such structures usually are affected by. Basing on a sol-gel TiO2 matrix, a new material has been conceived, embedding a low index dielectric (Polyvinylpyrrolidone, PVP) and an organic fluorescent medium (Coumarin C500). It has been found that the unsintered sol-gel TiO2 remains extremely sensitive to any temperature change, endowing the HMM embedding such new mixture with thermally tunable features. The possibility to thermally reversibly reconfigure the most significant properties of an HMM embedding such a new dielectric has been both theoretically and experimentally demonstrated as well those one of a complete reconfiguration of the system, irreversibly switching from an effective metal to an effective dielectric, when exposed to high temperatures. In the end, it has been possible to theorize and study a new propagation regime called Resonant Gain, occurring in specifically modified eNZP HMMs. In order the resonant gain singularity to occur in the perpendicular dielectric permittivity of the eNZP HMM, a fluorescent medium has to embedded in the dielectric layers. Conditions to fulfil are very stringent but, once reached, it has been demonstrated that light propagating in such a regime is extremely subwavelength confined and amplificated inside the HMM, giving rise to a self-amplifying perfect lens and leading this system to configure as a promising candidate for LASER effect at the nanoscale. The same phenomenon has been verified in the framework of newly conceived system consisting in dye embedding metal/dielectric multishell nanoparticle, configuring as promising candidates for SPASER effect.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXIX SSD FIS/03-FIS/07
Keywords: Metamaterials; Plasmons (Physics)